The Effect of Interactive PowerPoint Media Design on Student Learning Interests - Anggun Apriliani Zahra Rosyiddin; Amir Fiqih; Hafsah Nugraha; Angga Hadiapurwa; Diemas Arya Komara (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
This research was conducted to determine the influence of design in interactive Powerpoint media on student learning interest and how the influence of interactive Powerpoint media on student learning interest. The purpose of this study is based on the frequency of use of Powerpoint media in the learning process. Based on the author's hypothesis, there is an influence of interactive Powerpoint media on students' interest in learning. This influence is positive, meaning that interactive Powerpoint media can increase student interest in learning. The method used in this research is a quantitative method with data collection techniques using online questionnaires that are distributed to predetermined targets. The target of this research is active students from various universities in Indonesia. There are a total of 40 respondents in this research. The results of this research indicate that the difference in design of interactive PowerPoint media can increase students' learning interest.